PENGARUH KONTRAK PSIKOLOGIS DAN KETIDAKPUASAN TERHADAP INTENSI TURNOVER - , Stephanie Cinde Kanesworo; , Dr. Bagus Riyono, MA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
An employee turnover was a crucial problem facing by an organization. The company with too high employee turnover would encounter a serious problem. For the workers themselves, turnover was not something to expect. Turnover was a process affected by various kinds of conditions. This research was aimed to know the influence of a psychological contract towards a turnover intention. The gaps occurred of what was promised in a contract and what was perceived by employees would lead a satisfaction level decreased, so that eventually emerge dissatisfaction. In the previous researches, a dissatisfaction was generally would trigger a turnover intention. This research was also aimed to know a more specific dissatisfaction namely dissatisfaction towards a psychological contract. Hypothesis in this research was dissatisfaction would arise if there are gaps between what was promised and what was experienced and the dissatisfaction towards a psychological contract would strengthen a turnover intention. Subjects in this research were 55 salespeople in a banking company. To examine that hypothesis research subjects were asked to fill three questionnaires namely: a perception towards a psychological contract gap, dissatisfaction towards a psychological contract, and a turnover intention. This research result showed that perception towards a psychological contract gap did not actually significantly correlated to a dissatisfaction with Î² = 0.111 (Î²<1.96) and p = 0.418 (p>0.01), meanwhile, a dissatisfaction towards a psychological contract affected a turnover intention strength with Î² = 0.352 (Î²<1.96) and p = 0.008 (p<0.01) that showed that a dissatifaction contribution towards a psychological contract to a turnover intention was low. A determination coefficient R2 = 0.124 explained that a dissatisfaction towards a psychological contract perception only contributed 12.4% towards a turnover intention, while 87.6% were other variable contributions in the outside of a dissatisfaction towards a psychological contract perception. This showed that a perception towards a psychological contract gap and satisfaction were two different variables due to a job satisfaction variable was subjective in nature and also according to Dipboye, Smith, and Howell (1993),30% of them were affected by a personal factor. This research result supported a relationship hypothesis between dissatisfaction and turnover intention. A consequence of this result would be discussed in a discussion.